Hydrogenated copolymer, thermoplastic elastomer composition, and molded article

A hydrogenated copolymer with a specific structure addresses the compatibility and performance issues with polypropylene by achieving a balance of wear resistance, processability, and other properties in thermoplastic elastomer compositions.

JP7649134B2Active Publication Date: 2025-03-19ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020213232
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-23
Publication Date
2025-03-19
Estimated Expiration
2040-12-23

AI Technical Summary

Technical Problem

Existing hydrogenated copolymers are incompatible with thermoplastic resins like polypropylene, making it difficult to achieve compatibility, processability, wear resistance, and low-temperature properties in applications such as automobile parts and medical components.

Method used

A hydrogenated copolymer with a specific structure, containing vinyl aromatic monomer units and conjugated diene monomer units, is developed. This copolymer has distinct polymer blocks with varying content percentages of vinyl aromatic monomer units and is hydrogenated to achieve a balance between wear resistance, processability, and other properties.

Benefits of technology

The hydrogenated copolymer achieves a good balance of wear resistance, processability, and other properties when mixed with thermoplastic resins like polypropylene, enhancing the performance of thermoplastic elastomer compositions in various applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649134000001
    Figure 0007649134000001
  • Figure 0007649134000002
    Figure 0007649134000002
  • Figure 0007649134000003
    Figure 0007649134000003
Patent Text Reader

Abstract

To obtain a hydrogenated copolymer capable of improving wear resistance, workability and the balance of various characteristics in a thermoplastic elastomer composition mixed with polypropylene and a rubbery polymer.SOLUTION: There is provided a hydrogenated copolymer (X) comprising a hydrogenated copolymer (a) and a hydrogenated copolymer (b), wherein (a) has a polymer block A2 having a vinyl aromatic monomer unit content of 25 mass% or more and less than 80 mass%, the vinyl bond amount before hydrogenation of the block A2 is 1 mol% or more and less than 40 mol%, the Mw of (a) is 100000 or more, the hydrogenation rate of (a) is 70 mol% or more, (b) has a polymer block B2 having a vinyl aromatic monomer unit content of 1 mol% or more and less than 25 mass%, the vinyl bond amount before hydrogenation of the block B2 is 40 to 80 mol%, the Mw of (b) is less than 100000 and the mass ratio (a) / (b) of the content of (a) to the content of (b) is 1 / 99 to 99 / 1.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hydrogenated copolymer, a thermoplastic elastomer composition, and a molded article. [Background technology]

[0002] Hydrogenated copolymers of block copolymers using conjugated diene compounds and vinyl aromatic compounds have elasticity similar to that of natural rubber or synthetic rubber at room temperature, and at high temperatures they have moldability similar to that of thermoplastic resins. Furthermore, they have excellent weather resistance and heat resistance. Therefore, they have been widely used as resin modifiers in a wide range of fields, including automobile parts, medical molded products, asphalt modifiers, footwear, molded products such as food containers, packaging materials, adhesive sheets, and home appliance and industrial parts.

[0003] For example, Patent Document 1 discloses a hydrogenated copolymer which is a hydrogenated product of a non-hydrogenated copolymer having a random copolymer structure having conjugated diene monomer units and vinyl aromatic monomer units, and a resin composition containing the hydrogenated copolymer and a thermoplastic resin or a rubber-like polymer. This resin composition has excellent mechanical properties and abrasion resistance, and is therefore used as an alternative material to soft polyvinyl chloride resin. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2004 / 003027 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the hydrogenated copolymer disclosed in Patent Document 1 has poor compatibility with thermoplastic resins such as polypropylene, and further has poor processability and mechanical properties at low temperatures, making it difficult to apply the copolymer to applications requiring compatibility with polypropylene, processability, abrasion resistance, and low-temperature properties, such as automobile parts and medical parts. In the fields of automotive components such as automotive interior skin materials, medical components such as infusion bags and infusion tubes, adhesive films based on polyolefins, and food and clothing packaging, the properties required of resin compositions include excellent abrasion resistance, good processability, and a good balance of each property, but resins and thermoplastic elastomer compositions that satisfy these properties have not yet been obtained. In particular, in applications such as automotive interior materials, improved design and efficient molding are required, and if the viscosity of the resins and thermoplastic elastomer compositions used as materials is high, there is a risk that moldability will deteriorate and poor appearance will occur. At the same time, there is a demand for hydrogenated copolymers which can simultaneously achieve practically sufficient abrasion resistance and low shear viscosity.

[0006] In view of the above-mentioned problems in the conventional art, the present invention has an object to provide a hydrogenated copolymer which, when mixed with a thermoplastic resin such as polypropylene or a rubber-like polymer, can provide a thermoplastic elastomer composition having excellent abrasion resistance, good processability, and a good balance of each property at a high level. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted intensive studies to solve the above problems, and as a result have found that a hydrogenated copolymer having a specific structure can solve the above problems of the conventional techniques, thereby completing the present invention. That is, the present invention is as follows.

[0008] [1] Hydrogenated polymers containing vinyl aromatic monomer units and conjugated diene monomer units A hydrogenated copolymer (X) containing a copolymer (a) and a hydrogenated copolymer (b), The hydrogenated copolymer (a) contains vinyl aromatic monomer units and conjugated diene monomer units. , A polymer block having a vinyl aromatic monomer unit content of 25% by mass or more and less than 80% by mass. Has QA2, The amount of vinyl bonds in the polymer block A2 before hydrogenation of the hydrogenated copolymer (a) is 1 mol % or less. and less than 40 mol%. The hydrogenated copolymer (a) has a weight average molecular weight of 100,000 or more, 70 mol % or more of the total conjugated diene monomer units of the hydrogenated copolymer (a) are hydrogenated. And, The hydrogenated copolymer (b) contains vinyl aromatic monomer units and conjugated diene monomer units. A polymer block having a vinyl aromatic monomer unit content of 1% by mass or more and less than 25% by mass. B2, The amount of vinyl bonds in the polymer block B2 of the hydrogenated copolymer (b) before hydrogenation is 40 mol%. or more and 80 mol% or less, The weight average molecular weight of the hydrogenated copolymer (b) is less than 100,000; The content of the hydrogenated copolymer (a) and the mass ratio of the hydrogenated copolymer (b) to the content of the hydrogenated copolymer (a) ( A hydrogenated copolymer (X), in which a) / (b) is 1 / 99 to 99 / 1. [2] The above The method according to [1] A hydrogenated copolymer (X), A thermoplastic resin and / or a rubbery polymer; A thermoplastic elastomer composition comprising: [3] A molded article of the thermoplastic elastomer composition described in [2] above. Effect of the Invention

[0009] According to the present invention, there is obtained a hydrogenated copolymer which, when mixed with a thermoplastic resin such as polypropylene or a rubber-like polymer, can form a thermoplastic elastomer composition having a good balance of abrasion resistance, processability and other properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment for carrying out the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the following content, and can be carried out in various modifications within the scope of the gist of the present invention.

[0011] [Hydrogenated copolymer (X)] The hydrogenated copolymer (X) of the present embodiment is a copolymer of a vinyl aromatic monomer unit and a conjugated diene monomer unit. The present invention relates to a hydrogenated copolymer (a) and a hydrogenated copolymer (b) obtained by hydrogenating a polymer containing a unit, The hydrogenated copolymer (a) contains vinyl aromatic monomer units and conjugated diene monomer units, The polymer block A2 has a vinyl aromatic monomer unit content of 25% by mass or more and less than 80% by mass, the amount of vinyl bonds in the polymer block A2 of the hydrogenated copolymer (a) before hydrogenation is 1 mol % or more and less than 40 mol %, The hydrogenated copolymer (a) has a weight average molecular weight of 100,000 or more, 70 mol % or more of all conjugated diene monomer units of the hydrogenated copolymer (a) are hydrogenated, The hydrogenated copolymer (b) has a polymer block B2 containing a vinyl aromatic monomer unit and a conjugated diene monomer unit, and the content of the vinyl aromatic monomer unit is 1% by mass or more and less than 25% by mass, the amount of vinyl bonds in the polymer block B2 of the hydrogenated copolymer (b) before hydrogenation is 40 mol % or more and 80 mol % or less; The weight average molecular weight of the hydrogenated copolymer (b) is less than 100,000; a mass ratio (a) / (b) of the content of the hydrogenated copolymer (a) to the content of the hydrogenated copolymer (b) is 1 / 99 to 99 / 1; Hydrogenated copolymer (X). The hydrogenated copolymer (X) of the present embodiment has the above-mentioned constitution, and therefore when mixed with a thermoplastic resin such as polypropylene or a rubber-like polymer, the resulting thermoplastic elastomer composition exhibits a good balance of abrasion resistance, processability, and other properties. Each component will be described in detail below.

[0012] In this specification, with regard to a monomer unit constituting a polymer block, the term "mainly composed of" means that the target monomer unit is contained in the target polymer block in an amount of 80% by mass or more and 100% by mass or less, preferably 90% by mass or more and 100% by mass or less.

[0013] (vinyl aromatic compounds) Examples of vinyl aromatic compounds used to form the vinyl aromatic monomer units constituting the hydrogenated copolymer (a) and the hydrogenated copolymer (b) contained in the hydrogenated copolymer (X) of the present embodiment include, but are not limited to, styrene, α-methylstyrene, p-methylstyrene, divinylbenzene, 1,1-diphenylethylene, N,N-dimethyl-p-aminoethylstyrene, and N,N-diethyl-p-aminoethylstyrene. Among these, styrene, α-methylstyrene, and 4-methylstyrene are preferred from the viewpoints of availability and productivity. From the viewpoint of reactivity, the vinyl aromatic monomer unit contained in a block containing a vinyl aromatic monomer unit and a conjugated diene monomer unit (so-called random block) is preferably styrene. These may be used alone or in combination of two or more.

[0014] (Conjugated diene compounds) The conjugated diene compound used to form the conjugated diene monomer units constituting the hydrogenated copolymer (a) and the hydrogenated copolymer (b) contained in the hydrogenated copolymer (X) of the present embodiment is not particularly limited as long as it is a diolefin having a conjugated double bond, and examples thereof include 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, and 1,3-hexadiene. Among these, 1,3-butadiene and isoprene are preferred from the viewpoints of availability and productivity. These may be used alone or in combination of two or more.

[0015] (Hydrogenation rate) In the hydrogenated copolymer (X) of the present embodiment, it is preferred that the hydrogenated copolymer (a) constituting the hydrogenated copolymer (X) has 70 mol % or more of all conjugated diene monomer units hydrogenated, and the hydrogenated copolymer (b) has 70 mol % or more of all conjugated diene monomer units hydrogenated. Since the hydrogenation rate also affects the solubility parameter value, fluidity, and glass transition temperature of the copolymer, a preferable hydrogenation rate is set taking into consideration the effects on these. That is, the hydrogenation rate of all conjugated diene monomer units of the hydrogenated copolymer (a) and the hydrogenated copolymer (b) (hydrogenation rate of carbon-carbon double bonds derived from conjugated diene units) is preferably 70 mol% or more, more preferably 85 mol% or more, and even more preferably 95 mol%, with no particular upper limit. When the hydrogenation rates of the hydrogenated copolymers (a) and (b) are 70 mol% or more, the solubility parameter values ​​of the hydrogenated copolymer (X) of the present embodiment and polypropylene become closer to each other, and the dispersibility becomes good. In addition, the blocking resistance of the hydrogenated copolymer (X) also becomes good, so that the wear resistance, processability, and low stickiness of the thermoplastic elastomer composition using the hydrogenated copolymer (X) are improved. The hydrogenation rate can be controlled, for example, by adjusting the amount of catalyst used during hydrogenation, and the hydrogenation rate can be controlled, for example, by adjusting the amount of catalyst used during hydrogenation, the amount of hydrogen fed, the pressure, and the temperature. This hydrogenation rate can be measured by proton nuclear magnetic resonance ( 1 It can be measured by H-NMR.

[0016] (Hydrogenated copolymer (a)) The hydrogenated copolymer (X) of the present embodiment contains the hydrogenated copolymer (a). The hydrogenated copolymer (a) has a polymer block A2 (hereinafter sometimes referred to as polymer block A2) which contains a vinyl aromatic monomer unit and a conjugated diene monomer unit and has a vinyl aromatic monomer unit content of 25 mass% or more and less than 80 mass%. Furthermore, the hydrogenated copolymer (a) preferably has at least one block mainly composed of a vinyl aromatic compound (hereinafter, sometimes referred to as polymer block A1). The hydrogenated copolymer (a) preferably has a structure represented by the following general formula, for example. The hydrogenated copolymer (a) may be a mixture containing a plurality of types of the following structures in any ratio.

[0017] (A1-A2) n A1-(A2-A1) n A2-(A1-A2) n [(A1-A2) n ] m -Z [(A2-A1) n ] m -Z [(A1-A2) n -A1] m -Z [(A2-A1) n -A2] m -Z

[0018] In each of the general formulae representing the hydrogenated copolymer (a) described above, A1 is a polymer block mainly composed of vinyl aromatic monomer units, and A2 is a polymer block containing vinyl aromatic monomer units and conjugated diene monomer units and having a vinyl aromatic monomer unit content of 25 mass% or more and less than 80 mass%.

[0019] The polymer block A2 contains a vinyl aromatic monomer unit and a conjugated diene monomer unit, and the content of the vinyl aromatic monomer unit is 25% by mass or more and less than 80% by mass. This allows the polymer block A1 and the polymer block A2 to be clearly distinguished. The boundary between the polymer block A1 and the polymer block A2 does not necessarily have to be clearly distinguished.

[0020] In each formula representing the hydrogenated copolymer (a), n is an integer of 1 or more, and preferably an integer of 1-5. m is an integer of 2 or more, preferably an integer of 2 to 12, and more preferably an integer of 2 to 8. Z represents a residue of a coupling agent. The coupling agent is not limited to the following, but examples thereof include polyhalogen compounds and acid esters described below.

[0021] When the polymer block A1 is a copolymer of vinyl aromatic monomer units and other monomer units, the vinyl aromatic monomer units in the polymer block A1 may be distributed uniformly or tapered, and there may be a plurality of uniformly distributed portions and / or a plurality of tapered portions. Furthermore, the polymer block A1 may have a plurality of portions with different contents of vinyl aromatic monomer units. The vinyl aromatic monomer units in the polymer block A2 may be distributed uniformly or in a tapered shape. The vinyl aromatic monomer units may have a plurality of uniformly distributed portions and / or a plurality of taperedly distributed portions. The polymer block A2 may have a plurality of portions with different contents of the vinyl aromatic monomer units.

[0022] <Total vinyl aromatic compound content> The content of all vinyl aromatic monomer units in the hydrogenated copolymer (a) is preferably from 30 to 90% by mass, more preferably from 35 to 80% by mass, and further preferably from 40 to 70% by mass. The content of the conjugated diene monomer unit in the hydrogenated copolymer (a) is preferably from 10% by mass to 70% by mass, more preferably from 20% by mass to 65% by mass, and further preferably from 30% by mass to 60% by mass. When the total content of the vinyl aromatic compounds in the hydrogenated copolymer (a) is 30% by mass or more, the thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment tends to have excellent abrasion resistance.When the total content of the vinyl aromatic compounds is 90% by mass or less, the thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment tends to have excellent low-temperature mechanical properties. The total content of vinyl aromatic compounds can be calculated by measuring the absorption intensity at 262 nm using an ultraviolet spectrophotometer according to the method described in the Examples below.

[0023] <Content of vinyl aromatic monomer unit in polymer block A2> The content of the vinyl aromatic monomer unit in the polymer block A2 in the hydrogenated copolymer (a) is 25% by mass or more and less than 80% by mass. The upper limit of the content is more preferably 75% by mass, and even more preferably 70% by mass. The lower limit of the content is preferably 30% by mass, more preferably 35% by mass, and even more preferably 40% by mass. When the content of vinyl aromatic monomer units in the polymer block A2 in the hydrogenated copolymer (a) is 25 mass% or more, the effect of providing a thermoplastic elastomer composition of the hydrogenated copolymer (X) of this embodiment, and a polypropylene resin or a rubber-like polymer having excellent abrasion resistance can be obtained. When the content of the vinyl aromatic compound is less than 80 mass %, the effect of the thermoplastic elastomer composition being excellent in low-temperature mechanical properties can be obtained. The content of the vinyl aromatic monomer unit in the polymer block A2 can be controlled within the above-mentioned numerical range by adjusting the amount of the vinyl aromatic compound fed during polymerization, and can be measured by a nuclear magnetic resonance (NMR) spectrometer.

[0024] <Content of Polymer Block A1> In the hydrogenated copolymer (a), the content of the polymer block A1 mainly composed of the vinyl aromatic monomer unit is preferably 1 mass % to 40 mass %, more preferably 5 mass % to 35 mass %, and further preferably 10 mass % to 30 mass %, based on the total mass of the hydrogenated copolymer (a). When the content of the polymer block A1 in the hydrogenated copolymer (a) is 1 mass% or more, the thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment tends to be excellent in CS (compression set (C-set)) and low stickiness. When the content of the block polymer A1 is 40% by mass or less, the thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment tends to be excellent in low-temperature mechanical properties and processability. The content of the polymer block A1 can be controlled by adjusting the amount of the monomer fed.

[0025] The content of polymer block A1 in the hydrogenated copolymer (a) can be calculated using the mass of a polymer mainly composed of vinyl aromatic monomer units (however, vinyl aromatic compounds having an average degree of polymerization of about 30 or less are excluded) determined by a method of oxidatively decomposing the unhydrogenated copolymer (a') with t-butyl hydroperoxide using osmium tetroxide as a catalyst (the method described in I. M. KOLTHOFF, et al., Polym. Sci. 1, 429 (1946)) (hereinafter referred to as the osmium tetroxide decomposition method).

[0026] The content of the polymer block A1 in the hydrogenated copolymer (a) can be measured by a nuclear magnetic resonance (NMR) spectrometer using the copolymer after hydrogenation (hydrogenated copolymer (a)) according to the method described in Y. Tanaka, et al., RUBBER CHEMISTRY and TECHNOLOGY 54, 685 (1981). The NMR method will be specifically explained by taking as an example a case where the vinyl aromatic compound is styrene and the conjugated diene compound is 1,3-butadiene. A sample of 30 mg of hydrogenated copolymer (a) dissolved in 1 g of deuterated chloroform was used. 1 1 H-NMR was measured, and the content (Ns value) of polymer block A1 (polystyrene block in this case) was calculated from the ratio of the integrated value of chemical shifts from 6.9 ppm to 6.3 ppm to the total integrated value. Block styrene strength (b-St strength) = (integrated value of 6.9 ppm to 6.3 ppm) / 2 Random styrene strength (r-St strength) = (integrated value of 7.5 ppm to 6.9 ppm) - 3 × (b-St) Ethylene-butylene strength (EB strength) = Total integrated value - 3 x {(b-St intensity) + (r-St intensity)} / 8 Polystyrene block content (Ns value) obtained by NMR method =104×(b-St strength) / [104×{(b-St strength)+(r-St strength)}+56×(EB strength)] Here, there is a correlation represented by the following formula between the content of block polymer A in copolymer (a') before hydrogenation measured by the osmium tetroxide decomposition method (referred to as the "Os value") and the content of block polymer A1 in hydrogenated copolymer (a) after hydrogenation measured by the NMR method (referred to as the "Ns value"). Os value = -0.012 (Ns value)2 + 1.8 (Ns value) -13.0

[0027] <Vinyl bond content> In the hydrogenated copolymer (a), the vinyl bond content in the conjugated diene monomer unit of the polymer block A2 before hydrogenation is from 1 mol % to less than 40 mol %, preferably from 5 mol to 38 mol %, more preferably from 10 mol to 37 mol %. Since the amount of vinyl bonds in the conjugated diene monomer units of the polymer block A2 of the hydrogenated copolymer (a) before hydrogenation is 1 mol % or more, the compatibility between the hydrogenated copolymer (X) and the polypropylene resin in the thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment is excellent. In addition, the thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment tends to be excellent in abrasion resistance, processability, and low-temperature mechanical properties. The vinyl bond portion before hydrogenation becomes ethylene bonded to the main chain after hydrogenation. Since this structure is similar to that of polypropylene in which methyl is bonded to the main chain as a side chain, it is considered that the greater the amount of vinyl bonds before hydrogenation, the greater the compatibility between the two and the closer the solubility parameter values ​​become. When the amount of vinyl bonds before hydrogenation is less than 40 mol %, the thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment tends to have excellent abrasion resistance and low stickiness. In the present embodiment, the vinyl bond content refers to the total content of 1,2-vinyl bonds (conjugated dienes incorporated into the polymer via 1,2-bonds) and 3,4-vinyl bonds (conjugated dienes incorporated into the polymer via 3,4-bonds) relative to the total conjugated dienes (here, when 1,3-butadiene is used as the conjugated diene, the 1,2-vinyl bond content, and when isoprene is used as the conjugated diene, the 3,4-vinyl bond content). The vinyl bond content based on the conjugated diene before hydrogenation can be measured using a nuclear magnetic resonance (NMR) spectrometer. The microstructure (ratio of cis, trans, and vinyl) derived from the conjugated diene compound monomer unit in the hydrogenated copolymer (a) can be controlled by using a polar compound, etc., which will be described later.

[0028] <Weight average molecular weight> The weight average molecular weight of the hydrogenated copolymer (a) is 100,000 or more, preferably 100,000 to 800,000, more preferably 120,000 to 500,000, and further preferably 140,000 to 400,000. When the hydrogenated copolymer (a) has a weight average molecular weight of 100,000 or more, the thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment tends to have excellent abrasion resistance and low stickiness. When the weight average molecular weight of the hydrogenated copolymer (a) is 800,000 or less, flowability enabling molding process and molded appearance tend to be good. The weight average molecular weight of the hydrogenated copolymer (a) can be determined by using the molecular weight of a peak in a chromatogram measured by gel permeation chromatography (GPC) according to the method described in the Examples below, and a calibration curve (created using the peak molecular weight of the standard polystyrene) obtained by measuring commercially available standard polystyrene.

[0029] The shape of the molecular weight distribution of the hydrogenated copolymer (a) measured by GPC is not particularly limited, and the molecular weight distribution may be a polymodal molecular weight distribution having two or more peaks, or a monomodal molecular weight distribution having one peak. The weight average molecular weight of the hydrogenated copolymer (a) can be controlled by adjusting the amount of monomer added during the polymerization step, the amount of reaction initiator added, the polymerization time, and the polymerization temperature. The melt flow rate (MFR; according to ISO 1133) of the hydrogenated copolymer (a) is preferably in the range of 0.01 to 200 g / 10 min, more preferably 0.1 to 150 g / 10 min, and even more preferably 1.0 to 100 g / 10 min. When the hydrogenated copolymer (a) has an MFR of 0.01 g / 10 min or more, the flowability of the thermoplastic elastomer composition using the hydrogenated copolymer (X) of the present embodiment tends to be sufficiently ensured, and when it is 200 g / 10 min or less, the low stickiness of the obtained thermoplastic elastomer composition tends to be sufficiently ensured.

[0030] (Hydrogenated copolymer (b)) The hydrogenated copolymer (X) of the present embodiment contains the hydrogenated copolymer (b). The hydrogenated copolymer (b) has a polymer block (hereinafter sometimes referred to as polymer block B2) which contains a vinyl aromatic monomer unit and a conjugated diene monomer unit and has a vinyl aromatic monomer unit content of 1% by mass or more and less than 25% by mass. Furthermore, the hydrogenated copolymer (b) preferably has at least one block mainly composed of vinyl aromatic monomer units (hereinafter, sometimes referred to as polymer block B1). The hydrogenated copolymer (b) preferably has a structure represented by the following general formula, for example: The hydrogenated copolymer (b) may be a mixture containing a plurality of the following structures in any ratio.

[0031] (B1-B2) n B1-(B2-B1) n B2-(B1-B2) n [(B1-B2) n ] m -Z [(B2-B1) n ] m -Z [(B1-B2) n -B1] m -Z [(B2-B1) n -B2] m -Z

[0032] In each of the general formulae representing the hydrogenated copolymer (b), B1 is a polymer block mainly composed of vinyl aromatic monomer units, and B2 is a polymer block containing vinyl aromatic monomer units and conjugated diene monomer units and having a vinyl aromatic monomer unit content of 1% by mass or more and less than 25% by mass.

[0033] The polymer block B2 contains a vinyl aromatic monomer unit and a conjugated diene monomer unit, and the content of the vinyl aromatic compound is 1% by mass or more and less than 25% by mass, whereby the polymer block B1 and the polymer block B2 are clearly distinguished from each other. The boundary between the polymer block B1 and the polymer block B2 does not necessarily have to be clearly distinguished. In the above formula, n is an integer of 1 or more, and preferably an integer of 1 to 5. m is an integer of 2 or more, preferably an integer of 2 to 12, and more preferably an integer of 2 to 8. Z represents a residue of a coupling agent. The coupling agent is not limited to the following, but examples thereof include polyhalogen compounds and acid esters described below.

[0034] When the polymer block B1 is a copolymer block of vinyl aromatic monomer units and other monomer units, the vinyl aromatic monomer units in the polymer block B1 may be distributed uniformly or in a tapered manner, and there may be a plurality of uniformly distributed portions and / or a plurality of tapered distributed portions. Furthermore, the polymer block B1 may contain a plurality of moieties having different contents of vinyl aromatic monomer units.

[0035] The vinyl aromatic monomer units in the polymer block B2 may be distributed uniformly or in a tapered shape. The vinyl aromatic monomer units may have a plurality of uniformly distributed portions and / or a plurality of taperedly distributed portions. The polymer block B2 may have a plurality of portions with different contents of the vinyl aromatic monomer units.

[0036] The hydrogenated copolymer (b) is preferably one polymerized by sequential polymerization. "Polymerized by sequential polymerization" means that the polymer is sequentially polymerized from one end of the final target polymer structure to the other end, without using a coupling reaction. Furthermore, it is preferable that the copolymer does not contain a coupling agent residue. When the hydrogenated copolymer (b) polymerized by sequential polymerization contains at least two polymer blocks B1 mainly composed of vinyl aromatic monomer units, this can form a network structure more effectively than a block copolymer containing only one polymer block B1 mainly composed of vinyl aromatic monomer units. Therefore, the thermoplastic elastomer composition obtained by using the hydrogenated copolymer (X) of this embodiment tends to have improved wear resistance and low-temperature mechanical properties. Therefore, it is preferable that the hydrogenated copolymer (b) has a small content of the block copolymer containing only one polymer block B1 mainly composed of vinyl aromatic monomer units.

[0037] For the same reasons as above, it is preferable that the hydrogenated copolymer (X) of this embodiment does not substantially contain a block copolymer having only one polymer block B1. The term "substantially free" means that the content of the block copolymer having only one polymer block B1 is not excluded even if the content is not intentionally included, but is unavoidably mixed in due to unintended deactivation of polymerization, etc. Specifically, the content of the block copolymer having only one polymer block B1 is preferably 3% by mass or less of the total amount, more preferably 2% by mass or less, and even more preferably 1% by mass or less.

[0038] <Total vinyl aromatic monomer unit content> The content of all vinyl aromatic monomer units in the hydrogenated copolymer (b) is preferably from 26 to 90% by mass, more preferably from 28 to 80% by mass, and further preferably from 30 to 70% by mass. The content of the conjugated diene monomer unit in the hydrogenated copolymer (b) is preferably from 10 to 74% by mass, more preferably from 20 to 72% by mass, and further preferably from 30 to 70% by mass. When the content of all vinyl aromatic monomer units in the hydrogenated copolymer (b) is 26 mass% or more, the thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment tends to have excellent abrasion resistance. When the content of all vinyl aromatic monomer units is 90 mass % or less, the thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment tends to have excellent low-temperature mechanical properties. The total content of vinyl aromatic compounds can be calculated by measuring the absorption intensity at 262 nm using an ultraviolet spectrophotometer according to the method described in the Examples below.

[0039] <Content of vinyl aromatic compound in polymer block B2> The content of the vinyl aromatic monomer unit in the polymer block B2 in the hydrogenated copolymer (b) is not less than 1% by mass and less than 25% by mass. The lower limit of the content is preferably 5% by mass, and more preferably 10% by mass. The upper limit of the content is preferably 22% by mass, and more preferably 20% by mass. If the content of vinyl aromatic monomer units in the hydrogenated copolymer (b) is 1% by mass or more, the thermoplastic elastomer composition of the hydrogenated copolymer (X) of the present embodiment with a polypropylene resin or a rubber-like polymer has excellent wear resistance. If the content of vinyl aromatic compounds is less than 25% by mass, the thermoplastic elastomer composition has excellent low-temperature mechanical properties. The content of the vinyl aromatic monomer unit can be controlled within the above-mentioned numerical range by adjusting the amount of the vinyl aromatic compound fed during polymerization, and can be measured by a nuclear magnetic resonance (NMR) spectrometer.

[0040] <Content of Polymer Block B1> The hydrogenated copolymer (b) preferably has a content of the polymer block B1 mainly composed of the vinyl aromatic compound of 18 mass% to 40 mass%, more preferably 19 mass% to 35 mass%, and further preferably 20 mass% to 30 mass%, based on the mass of the hydrogenated copolymer (b). When the content of the polymer block B1 in the hydrogenated copolymer (b) is 18% by mass or more, the thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment tends to be excellent in abrasion resistance, CS (compression set (C-set)), and low stickiness. When the content of the block polymer B1 is 40% by mass or less, the thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment tends to be excellent in low-temperature mechanical properties and processability. The content of the polymer block B1 in the hydrogenated copolymer (b) can be controlled by adjusting the amount of the monomer fed.

[0041] The content of polymer block B1 in the hydrogenated copolymer (b) can be calculated using the mass of a polymer mainly composed of a vinyl aromatic compound (however, vinyl aromatic compounds having an average degree of polymerization of about 30 or less are excluded) determined by a method of oxidatively decomposing the unhydrogenated copolymer (b') with t-butyl hydroperoxide using osmium tetroxide as a catalyst (the method described in I. M. KOLTHOFF, et al., Polym. Sci. 1, 429 (1946)) (hereinafter referred to as the osmium tetroxide decomposition method).

[0042] The content of the polymer block B1 in the hydrogenated copolymer (b) can be measured by a nuclear magnetic resonance (NMR) apparatus using the copolymer after hydrogenation (hydrogenated copolymer (b)) according to the method described in Y. Tanaka, et al., RUBBER CHEMISTRY and TECHNOLOGY 54, 685 (1981). The NMR method will be specifically explained by taking as an example a case where the vinyl aromatic compound is styrene and the conjugated diene compound is 1,3-butadiene. 30 mg of the hydrogenated copolymer (b) was dissolved in 1 g of deuterated chloroform and the 1H-NMR was measured to determine the content (Ns value) of the polymer block B1 (in this case, the polystyrene block) from the ratio of the integrated value of the chemical shift from 6.9 ppm to 6.3 ppm to the total integrated value. Block styrene strength (b-St strength) = (integrated value of 6.9 ppm to 6.3 ppm) / 2 Random styrene strength (r-St strength) = (integrated value of 7.5 ppm to 6.9 ppm) - 3 × (b-St) Ethylene-butylene strength (EB strength) = Total integrated value - 3 x {(b-St intensity) + (r-St intensity)} / 8 Polystyrene block content (Ns value) obtained by NMR method =104×(b-St strength) / [104×{(b-St strength)+(r-St strength)}+56×(EB strength)] Here, there is a correlation represented by the following formula between the content of block polymer B1 in copolymer (b') before hydrogenation measured by the osmium tetroxide decomposition method (referred to as the "Os value") and the content of block polymer B1 in hydrogenated copolymer (b) after hydrogenation measured by the NMR method (referred to as the "Ns value"). Os value = -0.012 (Ns value)2 + 1.8 (Ns value) -13.0

[0043] <Vinyl bond content> The vinyl bond amount of the polymer block B2 of the hydrogenated copolymer (b) before hydrogenation is 40 mol % to 80 mol %, preferably 42 mol % to 75 mol %, and more preferably 44 mol % to 70 mol %. Since the vinyl bond amount of the polymer block B2 of the hydrogenated copolymer (b) before hydrogenation is 40 mol % or more, in the thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment, the compatibility between the hydrogenated copolymer (X) and the polypropylene resin becomes excellent, and the thermoplastic elastomer composition tends to be excellent in abrasion resistance, processability and low-temperature mechanical properties. The vinyl bond portion before hydrogenation becomes ethylene bonded to the main chain after hydrogenation. Since this structure is similar to that of polypropylene in which methyl is bonded to the main chain as a side chain, it is considered that the greater the amount of vinyl bonds before hydrogenation, the greater the compatibility between the two and the closer the solubility parameter values ​​become.

[0044] In addition, since the vinyl bond amount of the polymer block B2 of the hydrogenated copolymer (b) before hydrogenation is 80 mol % or less, the thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment tends to have excellent abrasion resistance and low stickiness.

[0045] In the present embodiment, the vinyl bond content refers to the total content of 1,2-vinyl bonds (conjugated dienes incorporated into the polymer via 1,2-bonds) and 3,4-vinyl bonds (conjugated dienes incorporated into the polymer via 3,4-bonds) relative to the total conjugated dienes (here, when 1,3-butadiene is used as the conjugated diene, the 1,2-vinyl bond content, and when isoprene is used as the conjugated diene, the 3,4-vinyl bond content).

[0046] The vinyl bond content before hydrogenation of the polymer block B2 of the hydrogenated copolymer (b) can be measured by using a nuclear magnetic resonance (NMR) apparatus. The microstructure (ratio of cis, trans, vinyl) derived from the conjugated diene compound monomer units in the hydrogenated copolymer (b) can be controlled within a predetermined numerical range by using a polar compound described later and adjusting the amount of the polar compound added.

[0047] <Weight average molecular weight> The weight average molecular weight of the hydrogenated copolymer (b) is less than 100,000, preferably less than 90,000, and more preferably less than 80,000.

[0048] When the hydrogenated copolymer (b) has a weight average molecular weight of less than 100,000, the processability of the thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment tends to be excellent. The weight average molecular weight of the hydrogenated copolymer (b) can be determined by using the molecular weight of a peak in a chromatogram measured by gel permeation chromatography (GPC) according to the method described in the Examples below, and a calibration curve (created using the peak molecular weight of the standard polystyrene) obtained by measuring commercially available standard polystyrene. The shape of the molecular weight distribution of the hydrogenated copolymer (b) measured by GPC is not particularly limited, and the molecular weight distribution may be a polymodal molecular weight distribution having two or more peaks, or a monomodal molecular weight distribution having one peak.

[0049] The weight average molecular weight of the hydrogenated copolymer (b) can be controlled by adjusting the amount of monomer added during the polymerization step, the amount of reaction initiator added, the polymerization time, and the polymerization temperature.

[0050] The melt flow rate (MFR; in accordance with ISO 1133) of the hydrogenated copolymer (b) is preferably in the range of 30 to 500 g / 10 min, more preferably 40 to 300 g / 10 min, and further preferably 50 to 200 g / 10 min. When the hydrogenated copolymer (b) has an MFR of 30 g / 10 min or more, the flowability of the thermoplastic elastomer composition using the hydrogenated copolymer (X) of the present embodiment tends to be sufficiently ensured, and when the hydrogenated copolymer (b) has an MFR of 500 g / 10 min or less, the low stickiness of the thermoplastic elastomer composition tends to be sufficiently ensured.

[0051] (Mass ratio of hydrogenated copolymer (a) to hydrogenated copolymer (b) (hydrogenated copolymer (X)) In the hydrogenated copolymer (X) of the present embodiment, the mass ratio of the hydrogenated copolymer (a) to the hydrogenated copolymer (b), (a) / (b), is from the viewpoints of abrasion resistance, processability, and balance of each property of the thermoplastic elastomer composition containing the hydrogenated copolymer (X), and is preferably from 1 / 99 to 80 / 20, and more preferably from 1 / 99 to 70 / 30.

[0052] When the hydrogenated copolymer (X) contains the hydrogenated copolymer (a), the thermoplastic elastomer composition has excellent abrasion resistance. When the hydrogenated copolymer (X) contains the hydrogenated copolymer (b), the thermoplastic elastomer composition has excellent processability. Furthermore, when the hydrogenated copolymer (a) and the hydrogenated copolymer (b) are used in combination, the abrasion resistance is further improved and the balance of the processability and other properties (low stickiness, low-temperature mechanical properties) is excellent. The hydrogenated copolymer (X) of the present embodiment has the above-mentioned constitution, and therefore when mixed with a thermoplastic resin such as polypropylene or a rubber-like polymer, the resulting thermoplastic elastomer composition exhibits a good balance of abrasion resistance, processability, and other properties.

[0053] The method for producing the hydrogenated copolymer (X) of the present embodiment is not particularly limited, and examples thereof include: (1) a method in which the hydrogenated copolymer (a) and the hydrogenated copolymer (b) are polymerized and mixed before being recovered from the production solvent; (2) a method in which the hydrogenated copolymer (a) and the hydrogenated copolymer (b) are mixed after removing the solvent and catalyst from each of them; (3) a method in which a polymerization initiator is added in two stages during the polymerization reaction; and (4) a method in which a protic reagent such as an alcohol is added as a modifier for the living ends or a polymerization terminator during the polymerization reaction to terminate the reaction of a part of the living ends.

[0054] (Method for Producing Hydrogenated Copolymer (a) and Hydrogenated Copolymer (b)) Examples of methods for producing the hydrogenated copolymer (a) and the hydrogenated copolymer (b) include, but are not limited to, methods described in JP-B-36-19286, JP-B-43-17979, JP-B-46-32415, JP-B-49-36957, JP-B-48-2423, JP-B-48-4106, JP-B-51-49567, and JP-A-59-166518.

[0055] The hydrogenated copolymers (a) and (b) before hydrogenation can be obtained, for example, by a method of carrying out living anionic polymerization using a predetermined monomer in a hydrocarbon solvent using a polymerization initiator such as an organic alkali metal compound, but is not limited thereto.

[0056] The hydrocarbon solvent is not particularly limited, and examples thereof include aliphatic hydrocarbons such as n-butane, isobutane, n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclohexane, cycloheptane, and methylcycloheptane; and aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene.

[0057] As the polymerization initiator, an organic alkali metal compound that is generally known to have anionic polymerization activity toward conjugated diene compounds and vinyl aromatic compounds can be used. For example, there may be mentioned an aliphatic hydrocarbon alkali metal compound having 1 to 20 carbon atoms, an aromatic hydrocarbon alkali metal compound having 1 to 20 carbon atoms, an organic amino alkali metal compound having 1 to 20 carbon atoms, and the like. The alkali metal contained in the polymerization initiator is not limited to the following, but examples thereof include lithium, sodium, and potassium. One or more types of alkali metals may be contained in one molecule.

[0058] Examples of the polymerization initiator include, but are not limited to, n-propyllithium, n-butyllithium, sec-butyllithium, tert-butyllithium, n-pentyllithium, n-hexyllithium, benzyllithium, phenyllithium, tolyllithium, a reaction product of diisopropenylbenzene and sec-butyllithium, and a reaction product of divinylbenzene, sec-butyllithium, and a small amount of 1,3-butadiene. Furthermore, 1-(t-butoxy)propyllithium disclosed in U.S. Patent No. 5,708,092 and lithium compounds into which one or several molecules of an isoprene monomer have been inserted to improve the solubility thereof, siloxy group-containing alkyllithiums such as 1-(t-butyldimethylsiloxy)hexyllithium disclosed in British Patent No. 2,241,239, amino group-containing alkyllithiums disclosed in U.S. Patent No. 5,527,753, diisopropylamide lithium, hexamethyldisilazide lithium and other aminolithiums can also be used.

[0059] The amount of the lithium compound used as a polymerization initiator depends on the molecular weight of the target copolymer, but generally can be 0.01 to 0.5 phm (parts by mass per 100 parts by mass of monomer). The amount of the lithium compound used as a polymerization initiator is preferably 0.03 to 0.3 phm, more preferably 0.05 to 0.15 phm.

[0060] When a conjugated diene compound and a vinyl aromatic compound are copolymerized using an organic alkali metal compound as a polymerization initiator, a tertiary amine compound or an ether compound can be added as a vinyl bond amount regulator to adjust the content of vinyl bonds (1,2-bonds or 3,4-bonds) resulting from the conjugated diene compound incorporated in the copolymer and to adjust the random copolymerizability of the conjugated diene compound and the vinyl aromatic compound.

[0061] The tertiary amine compound is not particularly limited, but examples thereof include compounds represented by the following formula: R1R2R3N (In the formula, R1, R2, and R3 are a hydrocarbon group having 1 to 20 carbon atoms or a hydrocarbon group having a tertiary amino group.) Examples of such compounds include, but are not limited to, trimethylamine, triethylamine, tributylamine, N,N-dimethylaniline, N-ethylpiperidine, N-methylpyrrolidine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, 1,2-dipiperidinoethane, trimethylaminoethylpiperazine, N,N,N',N'',N''-pentamethylethylenetriamine, N,N'-dioctyl-p-phenylenediamine, etc. Among these, N,N,N',N'-tetramethylethylenediamine is preferred.

[0062] As the ether compound, a linear ether compound or a cyclic ether compound can be used. Examples of the linear ether compound include dialkyl ether compounds of ethylene glycol, such as dimethyl ether, diethyl ether, diphenyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and ethylene glycol dibutyl ether; and dialkyl ether compounds of diethylene glycol, such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, and diethylene glycol dibutyl ether. Examples of cyclic ether compounds include tetrahydrofuran, dioxane, 2,5-dimethyloxolane, 2,2,5,5-tetramethyloxolane, 2,2-bis(2-oxolanyl)propane, and alkyl ethers of furfuryl alcohol.

[0063] The amount of the tertiary amine compound or ether compound used is preferably 0.1 to 4 (mol / mol of alkali metal), more preferably 0.2 to 3 (mol / mol of alkali metal), relative to the amount of the polymerization initiator of the organic alkali metal compound.

[0064] In the process for producing the hydrogenated copolymers (a) and (b), sodium alkoxide may be present during copolymerization. The sodium alkoxide is, for example, a compound represented by the following formula, but is not limited thereto: In particular, sodium alkoxides having an alkyl group having 3 to 6 carbon atoms are preferred, and sodium t-butoxide and sodium t-pentoxide are more preferred. NaOR (wherein R is an alkyl group having 2 to 12 carbon atoms). The amount of sodium alkoxide used in the polymerization step of the hydrogenated copolymers (a) and (b) is preferably 0.01 or more and less than 0.1 (molar ratio), more preferably 0.01 or more and less than 0.08 (molar ratio), even more preferably 0.03 or more and less than 0.08 (molar ratio), and still more preferably 0.04 or more and less than 0.06 (molar ratio), relative to the vinyl bond amount regulator (tertiary amine compound or ether compound). When the amount of sodium alkoxide is within this range, it tends to be possible to produce at a high productivity a copolymer having a copolymer block containing a conjugated diene monomer unit with a high vinyl bond amount and a polymer block mainly composed of a vinyl aromatic monomer unit with a narrow molecular weight distribution, and having a narrow molecular weight distribution and high strength.

[0065] The method for copolymerizing a conjugated diene compound and a vinyl aromatic compound using an organic alkali metal compound as a polymerization initiator is not particularly limited, and may be batch polymerization, continuous polymerization, or a combination thereof. The polymerization temperature is not particularly limited, but is usually from 0 to 180°C, and preferably from 30 to 150°C. The time required for polymerization varies depending on the conditions, but is usually within 48 hours, and preferably 0.1 to 10 hours. It is also preferable to carry out the polymerization in an atmosphere of an inert gas such as nitrogen gas. The polymerization pressure is not particularly limited as long as it is within a pressure range sufficient to maintain the monomer and the solvent in a liquid phase within the above-mentioned polymerization temperature range.

[0066] Furthermore, at the end of the polymerization, a required amount of a coupling agent having two or more functional groups may be added to carry out a coupling reaction. The coupling agent having two or more functional groups is not particularly limited, and any known coupling agent can be used. Examples of bifunctional coupling agents include, but are not limited to, dihalogen compounds such as dimethyldichlorosilane and dimethyldibromosilane, acid esters such as methyl benzoate, ethyl benzoate, phenyl benzoate, and phthalates. Examples of polyfunctional coupling agents having three or more functional groups include, but are not limited to, polyalcohols having three or more valences, polyfunctional epoxy compounds such as epoxidized soybean oil and diglycidyl bisphenol A, halogenated silicon compounds represented by the formula R1(4-n)SiXn (wherein R1 is a hydrocarbon group having 1 to 20 carbon atoms, X is a halogen, and n is an integer of 3 or 4), and halogenated tin compounds. Examples of halogenated silicon compounds include, but are not limited to, methylsilyl trichloride, t-butylsilyl trichloride, silicon tetrachloride, and brominated versions of these compounds. Examples of the tin halide compound include, but are not limited to, polyvalent halogen compounds such as methyltin trichloride, t-butyltin trichloride, tin tetrachloride, etc. Dimethyl carbonate, diethyl carbonate, etc. can also be used.

[0067] The hydrogenated copolymers (a) and (b) may be copolymers obtained by subjecting the living ends of the copolymers obtained by the above-mentioned methods to an addition reaction with a modifier that generates a functional group-containing atomic group. Examples of functional group-containing atomic groups include, but are not limited to, atomic groups containing at least one functional group selected from the group consisting of a hydroxyl group, a carbonyl group, a thiocarbonyl group, an acid halide group, an acid anhydride group, a carboxyl group, a thiocarboxyl acid group, an aldehyde group, a thioaldehyde group, a carboxylate group, an amide group, a sulfonic acid group, a sulfonate group, a phosphoric acid group, a phosphoric acid ester group, an amino group, an imino group, a nitrile group, a pyridyl group, a quinoline group, an epoxy group, a thioepoxy group, a sulfide group, an isocyanate group, an isothiocyanate group, a silicon halide group, a silanol group, an alkoxy silicon group, a tin halide group, an alkoxy tin group, and a phenyl tin group.

[0068] Examples of modifying agents having a functional group-containing atomic group include, but are not limited to, tetraglycidyl meta-xylylene diamine, tetraglycidyl-1,3-bisaminomethylcyclohexane, ε-caprolactone, δ-valerolactone, 4-methoxybenzophenone, γ-glycidoxyethyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl dimethylphenoxysilane, bis(γ-glycidoxypropyl)methylpropoxysilane, 1,3-dimethyl-2-imidazolidinone, 1,3-diethyl-2-imidazolidinone, N,N'-dimethylpropylene urea, and N-methylpyrrolidone.

[0069] The amount of the modifier added is preferably from 0.01 to 40 parts by mass, more preferably from 0.1 to 20 parts by mass, and further preferably from 0.3 to 10 parts by mass, based on 100 parts by mass of the hydrogenated copolymer before modification. The temperature for the addition reaction of the modifying agent is preferably 0 to 150°C, more preferably 20 to 120°C. The time required for the modification reaction varies depending on the modification reaction conditions, but is preferably within 24 hours, and more preferably 0.1 to 10 hours.

[0070] The hydrogenation catalyst used for producing the hydrogenated copolymers (a) and (b) is not particularly limited, and for example, the hydrogenation catalysts described in JP-B-42-8704, JP-B-43-6636, JP-B-63-4841, JP-B-1-37970, JP-B-1-53851, JP-B-2-9041, etc. can be used. Preferred hydrogenation catalysts include titanocene compounds and / or mixtures with reducing organometallic compounds. The titanocene compound is not particularly limited, but examples thereof include compounds described in JP-A-8-109219, and specific examples thereof include compounds having at least one ligand having a (substituted) cyclopentadienyl structure, an indenyl structure, and a fluorenyl structure, such as biscyclopentadienyltitanium dichloride and monopentamethylcyclopentadienyltitanium trichloride. The reducing organometallic compound is not particularly limited, but examples thereof include organoalkali metal compounds such as organolithium compounds, organomagnesium compounds, organoaluminum compounds, organoboron compounds, and organozinc compounds.

[0071] The reaction temperature for the hydrogenation reaction is usually from 0 to 200°C, and preferably from 30 to 150°C. The pressure of hydrogen used in the hydrogenation reaction is preferably 0.1 to 30 MPa, more preferably 0.2 to 10 MPa, and further preferably 0.3 to 5 MPa. The reaction time for the hydrogenation reaction is usually 3 minutes to 10 hours, and preferably 10 minutes to 5 hours.

[0072] The hydrogenation reaction may be carried out by any of a batch process, a continuous process, or a combination thereof. After completion of the hydrogenation reaction, catalyst residues may be removed from the reaction solution, if necessary. Methods for separating the hydrogenated copolymer from the solvent include, but are not limited to, a method in which a polar solvent that is a poor solvent for the hydrogenated copolymer, such as acetone or alcohol, is added to a solution of the hydrogenated copolymer to precipitate and recover the hydrogenated copolymer; a method in which the solution of the hydrogenated copolymer is poured into hot water with stirring and the solvent is removed by steam stripping to recover the hydrogenated copolymer; and a method in which the solvent is distilled off by directly heating the solution of the hydrogenated copolymer. The hydrogenated copolymer of the present embodiment may contain an antioxidant on its surface and / or inside, for example, by adding an antioxidant during the production.

[0073] The following antioxidant may also be added to the resin composition of the present embodiment, which will be described later. Examples of the antioxidant include, but are not limited to, phenol-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and amine-based antioxidants. Specifically, 2,6-di-t-butyl-4-methylphenol, n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butyl-phenyl)propionate, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane], tris-(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, 4,4'-butylidene-bis-(3-methyl-6-t-butylphenol), 3,9-bis[2-{3-(3-t-butyl-4-hydroxy-5-methyl n-octylthio)-6-(4-hydroxy-3,5-di-t-butylanilino)-1,3,5-triazine, pentaerythrityl-tetrakis[3 -(3,5-di-t-butyl-4-hydroxyphenyl)propionate], 2,2-thio-diethylenebis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], N,N'-hexamethylenebis(3,5-di-t-butyl-4-hydroxy-hydrocinnamamide), 3,5-di-t-butyl-4-hydroxybenzylphosphonate-diethyl ester, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, bis(3,5-di-t-butyl-4 -Hydroxybenzylphosphonic acid ethyl) calcium and polyethylene wax (50%) mixture, octylated diphenylamine, 2,4-bis[(octylthio)methyl]-o-cresol, isooctyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, butyric acid, 3,3-bis(3-t-butyl-4-hydroxyphenyl)ethylene ester, 1,1,3-tris-(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-tris(4-t-butyl-3-hydroxy-2,6-dimethylbenzyl) isocyanurate, 2-t-butyl-6-(3'-t-butyl-5'-methyl-2'-hydroxybenzyl)-4-methylphenyl-acrylate, and 2-[1-(2-hydroxy-3,5-di-t-pentylphenyl)-ethyl]-4,6-di-t-pentylphenyl acrylate.

[0074] The hydrogenated copolymers (a) and (b) may be pelletized. Examples of the pelletizing method include a method in which the hydrogenated copolymers (a) and (b) are extruded in the form of strands from a single-screw or twin-screw extruder and then cut in water with a rotary blade installed in front of a die section; a method in which the hydrogenated copolymer is extruded in the form of strands from a single-screw or twin-screw extruder, cooled with water or air, and then cut with a strand cutter; and a method in which the copolymer is melt-mixed using an open roll or Banbury mixer, formed into a sheet using a roll, the sheet is further cut into strips, and then cut into cubic pellets using a pelletizer. The size and shape of the pellets of the hydrogenated copolymers (a) and (b) are not particularly limited.

[0075] If necessary, a pellet anti-blocking agent may be blended with the pellets of the hydrogenated copolymers (a) and (b) in order to prevent blocking between the pellets. Examples of pellet blocking inhibitors include, but are not limited to, calcium stearate, magnesium stearate, zinc stearate, polyethylene, polypropylene, ethylene bisstearylamide, talc, and amorphous silica. The amount of the pellet antiblocking agent to be added is preferably 500 to 10,000 ppm, more preferably 1,000 to 5,000 ppm, based on the hydrogenated copolymers (a) and (b). The pellet antiblocking agent is preferably added in a state of adhering to the pellet surface, but may also be contained to some extent inside the pellet.

[0076] [Thermoplastic elastomer composition] The thermoplastic elastomer composition of the present embodiment is a composition comprising the hydrogenated copolymer (X) of the present embodiment, which contains the above-mentioned hydrogenated copolymer (a) and the hydrogenated copolymer (b), and a thermoplastic resin and / or rubber. and a polymer having a crystalline structure. The thermoplastic elastomer composition is excellent in abrasion resistance, processability and balance of various performance properties.

[0077] Examples of thermoplastic resins include, but are not limited to, polyethylene, polypropylene, polyvinyl chloride, polyethylene terephthalate, polycaprolactone, acrylonitrile-butadiene-styrene resin, polystyrene, methacrylic resin, polyamide, polycarbonate, polybutylene terephthalate, polyphenylene sulfide, polyacetal, modified polyphenylene ether, polysulfone, acrylonitrile-styrene resin, and the like. These thermoplastic resins may be used alone or in combination of two or more.

[0078] In particular, polypropylene is preferred from the viewpoints of strength, oil resistance, hardness adjustment, and processability of the thermoplastic elastomer composition. Examples of polypropylene include homopolymers of propylene, crystalline copolymers mainly composed of propylene, and block polypropylenes containing an olefin-based elastomer.

[0079] Examples of the copolymer include block copolymers, random copolymers, and block-random copolymers. Examples of the copolymer include crystalline propylene-based polymers such as isotactic polypropylene, propylene-ethylene copolymer, propylene-butene-1 copolymer, and propylene-ethylene-butene-1 terpolymer.

[0080] The rubber-like polymer comprises at least one polymer block S mainly made of a vinyl aromatic compound and at least one polymer block B mainly made of a conjugated diene compound, and is obtained by hydrogenating these polymer blocks. For example, the rubber-like polymer is a block copolymer of a vinyl aromatic compound and a conjugated diene compound having a structure such as SBS, BSBS, or SBSBS, or is obtained by hydrogenating the same (however, the hydrogenated copolymer (a) and the hydrogenated copolymer (b) of the present embodiment are excluded). This rubber-like polymer as a whole contains 20 to 60 mass %, preferably 30 to 50 mass %, of vinyl aromatic monomer units and 40 to 80 mass %, preferably 50 to 70 mass %, of conjugated diene monomer units, and it is preferable that 70% or more of the double bonds in the conjugated diene monomer units are hydrogenated.

[0081] The weight average molecular weight of the rubber-like polymer is preferably 200,000 to 1,000,000, more preferably 250,000 to 800,000, and further preferably 300,000 to 6,000,000. If the weight average molecular weight of the rubber-like polymer is 200,000 or more, sufficient mechanical strength tends to be obtained, and if the weight average molecular weight is 1,000,000 or less, molding processability tends to be good.

[0082] By mixing the above-mentioned hydrogenated copolymer (a) and hydrogenated copolymer (b), a thermoplastic resin and / or a rubber-like polymer, it is possible to obtain a thermoplastic elastomer composition having excellent abrasion resistance, processability and a balance of various performance properties. The composition may contain both the thermoplastic resin and the rubber-like polymer, or may contain only one of them. The ratio of the sum of the masses of the hydrogenated copolymers (a) and (b) contained in the thermoplastic elastomer composition to the total mass of the thermoplastic resin and the rubbery polymer (when only one of the thermoplastic resin and the rubbery polymer is contained, the mass of either one contained) is preferably [(a)+(b)] / (total of the thermoplastic resin composition and the rubbery polymer)=1 / 99 to 99 / 1, more preferably 10 / 90 to 90 / 10, and even more preferably 20 / 80 to 80 / 20. When the total mass content of the hydrogenated copolymer (a) and the hydrogenated copolymer (b) is within the above range, the thermoplastic elastomer composition has excellent abrasion resistance, processability and a balance of various performances. Furthermore, when the thermoplastic elastomer composition contains both a thermoplastic resin and a rubber-like polymer, the mass ratio of thermoplastic resin / rubber-like polymer is preferably 95 / 5 to 5 / 95, more preferably 80 / 20 to 20 / 80, and even more preferably 70 / 30 to 30 / 70.

[0083] The thermoplastic elastomer composition may contain a softening agent. Examples of the softener include paraffinic oil, naphthenic oil, aromatic oil, paraffin wax, liquid paraffin, white mineral oil, vegetable softener, etc. Among these, paraffinic oil, liquid paraffin, and white mineral oil are more preferable from the viewpoints of low-temperature properties and bleeding resistance of the thermoplastic elastomer composition and the molded article. The kinetic viscosity of the softener at 40°C is preferably 500mm 2 The lower limit of the kinetic viscosity of the softener at 40°C is not particularly limited, but is preferably 10 mm 2 The kinematic viscosity of the softener at 40°C is preferably 500 mm 2 / second or less, the flowability of the thermoplastic elastomer composition is improved, and the molding processability tends to be improved. The kinetic viscosity of the softener can be measured by a method using a glass capillary viscometer. In the thermoplastic elastomer composition of the present embodiment, the blending amount of the softener is preferably 5 to 100 parts by mass, more preferably 10 to 80 parts by mass, and further preferably 15 to 60 parts by mass, per 100 parts by mass of the total amount of the hydrogenated copolymer (X) of the present embodiment, the thermoplastic resin, and the rubber-like polymer.

[0084] The thermoplastic elastomer composition may further contain an olefin-based elastomer. Examples of olefin-based elastomers include α-olefin polymers or copolymers having 2 to 20 carbon atoms, and copolymers of ethylene and unsaturated carboxylic acids or unsaturated carboxylates. Examples of olefin-based elastomers include, but are not limited to, ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-4-methylpentene copolymers, ethylene-1-octene copolymers, propylene homopolymers, propylene-ethylene copolymers, propylene-ethylene-1-butene copolymers, 1-butene homopolymers, 1-butene-ethylene copolymers, 1-butene-propylene copolymers, 4-methylpentene homopolymers, 4-methylpentene-1-propylene copolymers, 4-methylpentene-1-butene copolymers, 4-methylpentene-1-propylene-1-butene copolymers, propylene-1-butene copolymers, ethylene-vinyl acetate copolymers, ethylene-methacrylic acid copolymers, and ethylene-methyl methacrylate copolymers.

[0085] The thermoplastic elastomer composition of the present embodiment may contain a tackifier. Examples of tackifiers include, but are not limited to, coumarone-indene resin, pt-butylphenol-acetylene resin, phenol-formaldehyde resin, xylene-formaldehyde resin, terpene resin, hydrogenated terpene resin, terpene-phenol resin, hydrogenated terpene phenol resin, aromatic modified terpene resin, aromatic modified hydrogenated phenol resin, styrene resin, alpha-methylstyrene resin, aromatic hydrocarbon resin, aliphatic hydrocarbon resin, aliphatic cyclic hydrocarbon resin, aliphatic and alicyclic petroleum resin, aliphatic and aromatic hydrocarbon resin, hydrogenated modified alicyclic hydrocarbon resin, hydrogenated alicyclic hydrocarbon resin, hydrocarbon tackifying resin, polybutene, liquid polybutadiene, cis-1,4-polyisoprene rubber, hydrogenated polyisoprene rubber, liquid polyisoprene rubber, and rosin resin.

[0086] The thermoplastic elastomer composition containing the hydrogenated copolymer of this embodiment may further contain other additives in addition to the above-mentioned components, so long as the object of the present invention is not impaired. Examples of such additives include heat stabilizers, antioxidants, UV absorbers, antioxidants, plasticizers, light stabilizers, crystal nucleating agents, impact modifiers, pigments, lubricants, antistatic agents, flame retardants, flame retardant assistants, compatibilizers, tackifiers, etc. These additives may be used alone or in combination of two or more.

[0087] (Method of producing thermoplastic elastomer composition) The method for producing the thermoplastic elastomer composition is not particularly limited, and it can be produced by a conventionally known method. For example, a melt-kneading method using a general mixer such as a pressure kneader, a Banbury mixer, an internal mixer, a lab plastomill, a mix lab, a single screw extruder, a twin screw extruder, a co-kneader, or a multi-screw extruder, or a method in which each component is dissolved or dispersed and mixed, and then the solvent is removed by heating, etc. are used. The shape of the thermoplastic elastomer is not particularly limited, and examples thereof include pellets, sheets, strands, and chips. In addition, after melt-kneading, it can be directly molded into a molded product.

[0088] [Molded Articles of Thermoplastic Elastomer Composition] The molded article of this embodiment is an article molded from the thermoplastic elastomer composition of this embodiment described above. The molded article of the thermoplastic elastomer composition of the present embodiment is excellent in abrasion resistance, processability, and a balance of various performances. Taking advantage of such properties, the article can be suitably used for extrusion molded articles, injection molded articles, blow molded articles, compressed air molded articles, vacuum molded articles, high-frequency fusion molded articles, overmolded articles, slush molded articles, and the like.

[0089] Specific applications of the material include, but are not limited to, automotive parts such as side moldings, grommets, shift knobs, weather strips, window frames and their sealing materials, arm rests, assist grips, door grips, door trims, handle grips, console boxes, head rests, instrument panels, bumpers, spoilers, and airbag covers. Examples of medical devices include, but are not limited to, medical tubes, medical hoses, catheters, blood bags, infusion bags, platelet storage bags, and artificial dialysis bags. Examples of building materials include, but are not limited to, wall materials, floor materials, and the like. Other examples include, but are not limited to, industrial hoses, food hoses, vacuum cleaner hoses, electrical cooling packing, various covering materials for electrical wires and the like, covering materials for grips, soft dolls, and the like. Examples of the fiber material include sound absorbing materials, clothing components, nonwoven fabrics for filters, and sanitary products. The molded article of this embodiment may be appropriately subjected to processing such as foaming, powdering, stretching, bonding, printing, painting, plating, and the like.

[0090] In recent years, autonomous driving and mobility services have been attracting attention as new directions for automobiles. This trend is also causing changes in the performance required for automotive interior materials. For example, with the advent of autonomous driving, it is expected that automobiles will play a stronger role as living spaces. Therefore, in order to create a more comfortable space for passengers, interiors are becoming more luxurious and interior designs are becoming more diverse. As a result, thermoplastic elastomer compositions used as materials for automobile interior materials are required to have better processability than ever before so that they can be molded into more intricate designs. From the viewpoint of mobility services, it is believed that the spread of car sharing will lead to increased demand for longer life and cleanliness of automobiles. Therefore, automobile interior materials will be cleaned more frequently than before, and the thermoplastic elastomer compositions used as materials for automobile interior materials will need to have higher abrasion resistance. Due to the spread of autonomous driving and mobility services as described above, in recent years, hydrogenated copolymers, which are materials for thermoplastic elastomer compositions, are required to have better processability and higher abrasion resistance than conventional products. However, in general, the processability and abrasion resistance of a hydrogenated copolymer are mutually contradictory physical properties that tend to be exhibited by the polymer structure. For example, by decreasing the molecular weight of the hydrogenated copolymer, the flowability of the hydrogenated copolymer tends to improve and the processability tends to increase, but on the other hand, the abrasion resistance tends to decrease. In consideration of the above-mentioned changes in performance required for automobile interior materials and the problems of hydrogenated copolymers, the thermoplastic elastomer composition containing the hydrogenated copolymer (X) of this embodiment has a low shear viscosity, which allows molding processing such as thin-wall molding to be carried out, and further has high abrasion resistance, so that it can withstand long-term use. In particular, it is suitable for molded products that require a high level of excellent abrasion resistance, processability, and balance of various performances. Examples of such products include packaging materials for food, beverages, medicines, precision instruments, etc., tubes (including catheters), bags, containers, trays, automobile parts and automobile interior skin materials (door trims, instrument panels, airbag covers, etc.), home appliances and OA equipment related parts, industrial parts, household goods, toys, etc. The above-mentioned extrusion molded products and injection molded products may be multi-layer extrusion molded products or multi-layer injection molded products. In this case, the hydrogenated copolymer of this embodiment or the above-mentioned thermoplastic elastomer composition may be used in all layers, or may be used in only one layer, or in two or more layers. EXAMPLES

[0091] The present invention will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples. First, the evaluation methods and the methods for measuring physical properties applied to the examples and comparative examples are described below.

[0092] [Method of identifying the structure of hydrogenated copolymer (a) and hydrogenated copolymer (b) and method of measuring physical properties] (Content of total vinyl aromatic monomer units in hydrogenated copolymer) The total content of vinyl aromatic monomer units in the hydrogenated copolymers (a) and (b) was measured by the following method. The total vinyl aromatic monomer unit content (mass%) of each copolymer was calculated from the absorption intensity at 262 nm using an ultraviolet spectrophotometer (Shimadzu Corporation, UV-2450) before hydrogenation. Incidentally, since the content of all vinyl aromatic monomer units does not change significantly before and after hydrogenation, the content of all vinyl aromatic monomer units (styrene monomer units) obtained for the copolymer before hydrogenation was taken as the content of all vinyl aromatic monomer units (total styrene content) of the hydrogenated copolymer.

[0093] (Contents of polymer block A1 and polymer block B1 in hydrogenated copolymer (Os value)) Polymer block A1 mainly composed of vinyl aromatic monomer units in hydrogenated copolymer (a) and the content of polymer block B1 mainly composed of vinyl aromatic monomer units in the hydrogenated copolymer (b) were measured by the following method. The copolymer before hydrogenation was measured by the osmium tetroxide decomposition method described in I. M. KOLTHOFF et al., J. Polym. Soi. 1, 429 (1946). To decompose the copolymer before hydrogenation, a 0.1 g / 125 mL tertiary butanol solution of osmic acid was used. The content of the polystyrene blocks obtained here was designated as the "Os value."

[0094] (Content of vinyl aromatic monomer units in polymer block A2 or B2) The content of vinyl aromatic monomer units in the polymer block A2 in the hydrogenated polymer block (a) and the content of vinyl aromatic monomer units in the polymer block B2 in the hydrogenated polymer block (b) were measured by the following method. The hydrogenated block copolymer was used as a measurement sample, and a polymer block mainly composed of vinyl aromatic monomer units and a polymer block composed of vinyl aromatic monomer units and conjugated diene monomer units were distinguished by proton nuclear magnetic resonance (1H-NMR, JOEL RESONABCE ECS400). Deuterated chloroform was used as the solvent, the sample concentration was 50 mg / mL, the observation frequency was 400 MHz, tetramethylsilane was used as the chemical shift standard, the pulse delay was 2.904 seconds, the number of scans was 256, and the measurement temperature was 23° C. From the integral intensity of the signal assigned to aromatics, the random and block aromatics were calculated from the integral value per 1H of each bonding mode, and then the total styrene content was calculated by the above-mentioned method, and the content ratio was calculated.

[0095] (Amount of vinyl bonds in polymer blocks A2 and B2) The vinyl bond amounts before hydrogenation of the polymer block A2 of the hydrogenated copolymer (a) and the polymer block B2 of the hydrogenated copolymer (b) were measured by the following method. The polymer samples taken at each step of the polymerization process of the copolymer before hydrogenation were measured for the vinyl bond amount (1,2-bond amount) by proton nuclear magnetic resonance (1H-NMR) using a nuclear magnetic resonance apparatus (BRUKER, DPX-400). Deuterated chloroform was used as the solvent, the sample concentration was 50 mg / mL, the observation frequency was 400 MHz, tetramethylsilane was used as the chemical shift standard, the pulse delay was 2.904 seconds, the number of scans was 64, the pulse width was 45°, and the measurement temperature was 26°C. The amount of vinyl bonds was calculated from the ratio of 1,2-bonds to the sum of 1,4-bonds and 1,2-bonds after calculating the integral value per 1H of each bond type from the integral values ​​of the signals assigned to 1,4-bonds and 1,2-bonds.

[0096] (Weight average molecular weight of hydrogenated copolymer) The weight average molecular weights of the hydrogenated copolymers (a) and (b) were measured by the following method. Measurements were performed using GPC (equipment: Tosoh HLC8220, column TSKgel SuperH-RC x 2). Tetrahydrofuran was used as the solvent. Measurements were performed at a temperature of 35°C. A calibration curve was created using commercially available standard polystyrene with a known weight average molecular weight, and the weight average molecular weight converted into polystyrene was calculated.

[0097] (Hydrogenation rate of hydrogenated copolymer (hydrogenation rate)) The hydrogenation rates of the hydrogenated copolymers (a) and (b) were measured by the following method. The hydrogenation rate of the hydrogenated copolymer was measured by a nuclear magnetic resonance apparatus (BRUKER, DPX-400). The hydrogenated copolymer, which is the copolymer after hydrogenation, was used to measure by proton nuclear magnetic resonance (1H-NMR). Specifically, the integral values ​​of the signal derived from the residual double bond at 4.5 to 5.5 ppm and the signal derived from the hydrogenated conjugated diene were calculated, and the ratio was calculated.

[0098] [Production of Thermoplastic Elastomer Composition] The mixture was mixed in a ratio of rubber-like polymer / polypropylene resin / softener / hydrogenated copolymer (X) = 50 / 40 / 80 / 50 and melt-kneaded at a set temperature of 200°C using a twin-screw extruder (Japan Steel Works, Ltd., "TEX-30αII", cylinder diameter 30 mm) to obtain pellets of a thermoplastic elastomer composition. Molding was performed at an injection molding temperature of 210° C. and a mold temperature of 40° C. to obtain a molded article of the thermoplastic elastomer composition (thickness 2.0 mm, with leather grain). The hydrogenated copolymer (X) is a hydrogenated copolymer based on the blending ratio (parts by mass) shown in Tables 3 to 5. The copolymers used were prepared using a1 to a14 which are (a) and b1 to b-12 which are hydrogenated copolymers (b). The polypropylene resin used was PM801A (homopolypropylene / Sunallomer; MFR (230° C., 2.16 kg)=15). The rubber-like polymer used was a styrene-based thermoplastic elastomer, Tuftec N504 (styrene content 32% by mass, manufactured by Asahi Kasei). The softener used was paraffin oil, PW-90 (manufactured by Idemitsu Kosan Co., Ltd.).

[0099] [Evaluation of physical properties of molded products of thermoplastic elastomer compositions] (Wear resistance) The abrasion resistance of the molded thermoplastic elastomer composition was evaluated by measuring the mass loss of the sample after rubbing the surface of the molded product (embossed leather surface) with a friction cloth Kanakin No. 3 cotton under a load of 500 g using a Gakushin type friction tester (AB-301 model, manufactured by Tester Sangyo Co., Ltd.). The smaller the mass loss, the higher the abrasion resistance of the thermoplastic elastomer composition is, and the evaluation was performed according to the following criteria. 5: After 10,000 friction cycles, the mass loss is less than 0.010g 4: After 10,000 friction cycles, the mass loss is 0.010g or more and less than 0.030g 3: After 10,000 friction cycles, the mass loss is 0.030g or more and less than 0.045g 2: After 10,000 friction cycles, the mass loss is 0.045g or more and less than 0.060g 1: After 10,000 friction cycles, the mass loss is 0.060g or more.

[0100] (processability) The processability of the thermoplastic elastomer composition was evaluated according to the following criteria by measuring the melt flow rate (MFR; in accordance with ISO 1133) of the hydrogenated copolymer (X). The temperature was 230° C. and the load was 2.16 kgf. 5: MFR is 15 or more 4: MFR is between 10 and 15 3: MFR is between 8 and 10 2: MFR is between 6 and 8 1: MFR is less than 6

[0101] (stickiness) The stickiness of the molded article of the thermoplastic elastomer composition was evaluated by the following method. The thermoplastic elastomer composition was press-molded at 200°C to produce a 2 mm-thick molded body. Two of these were stacked on top of each other (upper surface: 5 cm × 8 cm, lower surface: 4 cm × 5 cm), and then a 500 g load (dimensions: 6 cm × 10 cm × 1 cm) was placed on the upper surface and allowed to stand for 60 seconds. Thereafter, the tack strength (J) was measured when the sample was peeled off at 180° at a speed of 100 mm / min using a tensile tester (Minebea, Tg-5kN), and was used as an index of low stickiness and evaluated according to the following criteria. 5: Tack strength is less than 3N 4: Tack strength is 3N or more but less than 5N 3: Tack strength is 5N or more but less than 10N 2: Tack strength is 10N or more but less than 15N 1: Tack strength is 15N or more

[0102] (Low temperature elongation at break) The tensile elongation at break of the thermoplastic elastomer composition was evaluated by the following method. In accordance with JIS K6251, a tensile test was carried out using a thermostatic tensile tester (Minebea, Tg-5kN) at -30°C, No. 3 dumbbell, and a crosshead speed of 500 mm / min as follows, and the breaking elongation was evaluated. 4: Breaking elongation is 200% or more 3: Breaking elongation is 100% or more but less than 200% 2: Breaking elongation is 50% or more but less than 100% 1: Tensile modulus less than 50%

[0103] [Production of hydrogenated copolymer] (Preparation of hydrogenation catalyst) The hydrogenation catalyst used in the hydrogenation reaction of the copolymer was prepared by the following method. A nitrogen-purged reaction vessel was charged with 1 liter of dried and purified cyclohexane, and 100 mmol of biscyclopentadienyltitanium dichloride was added. With sufficient stirring, an n-hexane solution containing 200 mmol of trimethylaluminum was added, and the mixture was allowed to react at room temperature for approximately 3 days to obtain a hydrogenation catalyst.

[0104] (Hydrogenated copolymer) The hydrogenated copolymers (a-1) to (a-14) and the hydrogenated copolymers (b-1) to (b-12) were prepared as follows.

[0105] <Hydrogenated copolymer (a-1)> Batch polymerization was carried out using a tank-type reactor (internal volume: 10 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 20 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.084 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.35 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 70°C for 20 minutes. Next, a cyclohexane solution containing 47 parts by mass of styrene and a cyclohexane solution containing 33 parts by mass of butadiene (concentration: 20% by mass) were added and polymerized at 70° C. for 1 hour. Next, 0.25 mol of ethyl benzoate was added per mol of n-butyllithium, and the mixture was reacted at 70° C. for 10 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 67% by mass, a polymer block A1 content of 20% by mass, a vinyl bond amount in polymer block A2 before hydrogenation of 25%, and a weight average molecular weight of 193,000. The coupling rate determined from the peak area ratio of the GPC curve was 50%. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (a-1).

[0106] <Hydrogenated copolymer (a-2)> Batch polymerization was carried out using a tank-type reactor (internal volume: 10 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.067 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.35 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 70°C for 20 minutes. Next, a cyclohexane solution containing 47 parts by mass of styrene and a cyclohexane solution containing 33 parts by mass of butadiene (concentration: 20% by mass) were added and polymerized at 70° C. for 1 hour. Next, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 67% by mass, a polymer block A1 content of 20% by mass, a vinyl bond amount in polymer block A2 before hydrogenation of 18%, and a weight average molecular weight of 154,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (a-2).

[0107] <Hydrogenated copolymer (a-3)> Batch polymerization was carried out using a tank reactor (inner volume 10 L) equipped with a stirrer and a jacket. went. First, a cyclohexane solution containing 15 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.085 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.8 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 70°C for 5 minutes. Next, a cyclohexane solution containing 3 parts by mass of butadiene (concentration: 20% by mass) was added and polymerization was carried out at 70° C. for 5 minutes. Next, a cyclohexane solution containing 29 parts by mass of butadiene and 50 parts by mass of styrene (concentration: 20% by mass) was supplied so as to maintain a constant reaction temperature, and polymerization was carried out at 70° C. for 45 minutes. Next, a cyclohexane solution containing 3 parts by mass of butadiene was added, and polymerization was carried out at 70° C. for 5 minutes. Finally, 0.2 mol of tetraethoxysilane was added per mol of n-butyllithium, and the mixture was reacted at 70° C. for 30 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as described above had a styrene content of 65% by mass, a polymer block A1 content of 15% by mass, a vinyl bond amount of block copolymer A2 before hydrogenation of 23%, and a weight average molecular weight of 301,000. The coupling rate determined from the peak area ratio of the GPC curve was 70%. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (a-3).

[0108] <Hydrogenated copolymer (a-4)> Batch polymerization was carried out using a tank-type reactor (internal volume: 10 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 7.5 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.080 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.35 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 70°C for 20 minutes. Next, a cyclohexane solution containing 36 parts by mass of styrene and a cyclohexane solution containing 49 parts by mass of butadiene (concentration: 20% by mass) were added and polymerized at 70° C. for 1 hour. Next, a cyclohexane solution containing 7.5 parts by mass of styrene was added, and polymerization was carried out at 60° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 51% by mass, a polymer block A1 content of 15% by mass, a vinyl bond amount in polymer block A2 before hydrogenation of 22%, and a weight average molecular weight of 151,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (a-4).

[0109] <Hydrogenated copolymer (a-5)> Batch polymerization was carried out using a tank-type reactor (internal volume: 10 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.067 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.35 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 70°C for 20 minutes. Next, a cyclohexane solution containing 22 parts by mass of styrene and a cyclohexane solution containing 58 parts by mass of butadiene (concentration: 20% by mass) were added and polymerized at 70° C. for 1 hour. Next, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 42% by mass, a polymer block A1 content of 20% by mass, a vinyl bond amount in polymer block A2 before hydrogenation of 15%, and a weight average molecular weight of 154,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (a-5).

[0110] <Hydrogenated copolymer (a-6)> Batch polymerization was carried out using a tank-type reactor (internal volume: 10 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.067 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.35 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 70°C for 20 minutes. Next, a cyclohexane solution containing 62 parts by mass of styrene and a cyclohexane solution containing 18 parts by mass of butadiene (concentration: 20% by mass) were added and polymerized at 70° C. for 1 hour. Next, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 82% by mass, a polymer block A1 content of 20% by mass, a vinyl bond amount in polymer block A2 before hydrogenation of 30%, and a weight average molecular weight of 154,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (a-6).

[0111] <Hydrogenated copolymer (a-7)> Batch polymerization was carried out using a tank-type reactor (internal volume: 10 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.098 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.35 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 70°C for 20 minutes. Next, a cyclohexane solution containing 47 parts by mass of styrene and a cyclohexane solution containing 33 parts by mass of butadiene (concentration: 20% by mass) were added and polymerized at 70° C. for 1 hour. Next, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 67% by mass, a polymer block A1 content of 20% by mass, a vinyl bond amount in polymer block A2 before hydrogenation of 25%, and a weight average molecular weight of 105,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (a-7).

[0112] <Hydrogenated copolymer (a-8)> Batch polymerization was carried out using a tank-type reactor (internal volume: 10 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.067 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.50 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 70°C for 20 minutes. Next, a cyclohexane solution containing 47 parts by mass of styrene and a cyclohexane solution containing 33 parts by mass of butadiene (concentration: 20% by mass) were added and polymerized at 70° C. for 1 hour. Next, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 67% by mass, a polymer block A1 content of 20% by mass, a vinyl bond amount in polymer block A2 before hydrogenation of 38%, and a weight average molecular weight of 154,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (a-8).

[0113] <Hydrogenated copolymer (a-9)> Batch polymerization was carried out using a tank-type reactor (internal volume: 10 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.067 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.35 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 70°C for 20 minutes. Next, a cyclohexane solution containing 47 parts by mass of styrene and a cyclohexane solution containing 33 parts by mass of butadiene (concentration: 20% by mass) were added and polymerized at 70° C. for 1 hour. Next, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 67% by mass, a polymer block A1 content of 20% by mass, a vinyl bond amount in polymer block A2 before hydrogenation of 18%, and a weight average molecular weight of 154,000. Further, the hydrogenation catalyst prepared as described above was added to the obtained copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C, and the reaction was stopped midway. The hydrogenation rate of the resulting hydrogenated copolymer was 72%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (a-9).

[0114] <Hydrogenated copolymer (a-10)> Batch polymerization was carried out using a tank-type reactor (internal volume: 10 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.067 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.35 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 70°C for 20 minutes. Next, a cyclohexane solution containing 18 parts by mass of styrene and a cyclohexane solution containing 62 parts by mass of butadiene (concentration: 20% by mass) were added and polymerized at 70° C. for 1 hour. Next, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 38% by mass, a polymer block A1 content of 20% by mass, a vinyl bond amount in polymer block A2 before hydrogenation of 24%, and a weight average molecular weight of 154,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (a-10).

[0115] <Hydrogenated copolymer (a-11)> Batch polymerization was carried out using a tank-type reactor (internal volume: 10 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.067 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.35 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 70°C for 20 minutes. Next, a cyclohexane solution containing 67 parts by mass of styrene and a cyclohexane solution containing 13 parts by mass of butadiene (concentration: 20% by mass) were added and polymerized at 70° C. for 1 hour. Next, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 87% by mass, a polymer block A1 content of 20% by mass, a vinyl bond amount in polymer block A2 before hydrogenation of 22%, and a weight average molecular weight of 154,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (a-11).

[0116] <Hydrogenated copolymer (a-12)> Batch polymerization was carried out using a tank-type reactor (internal volume: 10 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.109 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.35 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 70°C for 20 minutes. Next, a cyclohexane solution containing 47 parts by mass of styrene and a cyclohexane solution containing 33 parts by mass of butadiene (concentration: 20% by mass) were added and polymerized at 70° C. for 1 hour. Next, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 67% by mass, a polymer block A1 content of 20% by mass, a vinyl bond amount in polymer block A2 before hydrogenation of 23%, and a weight average molecular weight of 95,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (a-12).

[0117] <Hydrogenated copolymer (a-13)> Batch polymerization was carried out using a tank-type reactor (internal volume: 10 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.067 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.80 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 70°C for 20 minutes. Next, a cyclohexane solution containing 47 parts by mass of styrene and a cyclohexane solution containing 33 parts by mass of butadiene (concentration: 20% by mass) were added and polymerized at 70° C. for 1 hour. Next, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 67% by mass, a polymer block A1 content of 20% by mass, a vinyl bond amount in polymer block A2 before hydrogenation of 45%, and a weight average molecular weight of 154,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (a-13).

[0118] <Hydrogenated copolymer (a-14)> Batch polymerization was carried out using a tank-type reactor (internal volume: 10 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added. Next, 0.067 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.35 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 70°C for 20 minutes. Next, a cyclohexane solution containing 47 parts by mass of styrene and a cyclohexane solution containing 33 parts by mass of butadiene (concentration: 20% by mass) were added and polymerized at 70° C. for 1 hour. Next, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 67% by mass, a polymer block A1 content of 20% by mass, a vinyl bond amount in polymer block A2 before hydrogenation of 18%, and a weight average molecular weight of 154,000. Further, the hydrogenation catalyst prepared as described above was added to the obtained copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C, and the reaction was stopped midway. The hydrogenation rate of the resulting hydrogenated copolymer was 65%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (a-14).

[0119] <Hydrogenated copolymer (b-1)> Batch polymerization was carried out using a tank-type reactor (internal volume: 100 L, charged cyclohexane: 36 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 12 parts by mass of styrene was added. Next, 0.136 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.8 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 65°C for 20 minutes. Next, a cyclohexane solution containing 13 parts by mass of styrene and a cyclohexane solution containing 64 parts by mass of butadiene (concentration: 40% by mass) were added and polymerized at 80° C. for 70 minutes. Next, a cyclohexane solution containing 11 parts by mass of styrene (concentration: 40% by mass) was added, and polymerization was carried out at 85° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as described above had a styrene content of 36% by mass, a polymer block B1 content of 23% by mass, a vinyl bond amount in polymer block B2 before hydrogenation of 50%, and a weight average molecular weight of 68,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (b-1).

[0120] <Hydrogenated copolymer (b-2)> Batch polymerization was carried out using a tank-type reactor (internal volume: 100 L, charged cyclohexane: 36 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 12 parts by mass of styrene was added. Next, 0.136 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.8 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 65°C for 20 minutes. Next, a cyclohexane solution containing 7 parts by mass of styrene and a cyclohexane solution containing 70 parts by mass of butadiene (concentration: 40% by mass) were added and polymerized at 80° C. for 70 minutes. Next, a cyclohexane solution containing 11 parts by mass of styrene (concentration: 40% by mass) was added, and polymerization was carried out at 85° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 30% by mass, a polymer block B1 content of 23% by mass, a vinyl bond amount in polymer block B2 before hydrogenation of 45%, and a weight average molecular weight of 68,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 99%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (b-2).

[0121] <Hydrogenated copolymer (b-3)> Batch polymerization was carried out using a tank-type reactor (internal volume: 100 L, charged cyclohexane: 36 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 12 parts by mass of styrene was added. Next, 0.136 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.8 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 65°C for 20 minutes. Next, a cyclohexane solution containing 18 parts by mass of styrene and a cyclohexane solution containing 59 parts by mass of butadiene (concentration: 40% by mass) were added and polymerized at 80° C. for 70 minutes. Next, a cyclohexane solution containing 11 parts by mass of styrene (concentration: 40% by mass) was added, and polymerization was carried out at 85° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 41% by mass, a polymer block B1 content of 23% by mass, a vinyl bond amount in polymer block B2 before hydrogenation of 53%, and a weight average molecular weight of 68,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (b-3).

[0122] <Hydrogenated copolymer (b-4)> Batch polymerization was carried out using a tank-type reactor (internal volume: 100 L, charged cyclohexane: 36 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 12 parts by mass of styrene was added. Next, 0.096 part by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.8 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 65°C for 20 minutes. Next, a cyclohexane solution containing 13 parts by mass of styrene and a cyclohexane solution containing 64 parts by mass of butadiene (concentration: 40% by mass) were added and polymerized at 80° C. for 70 minutes. Next, a cyclohexane solution containing 11 parts by mass of styrene (concentration: 40% by mass) was added, and polymerization was carried out at 85° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 36% by mass, a polymer block B1 content of 23% by mass, a vinyl bond amount in polymer block B2 before hydrogenation of 50%, and a weight average molecular weight of 96,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (b-4).

[0123] <Hydrogenated copolymer (b-5)> Batch polymerization was carried out using a tank-type reactor (internal volume: 100 L, charged cyclohexane: 36 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 12 parts by mass of styrene was added. Next, 0.210 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.8 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 65°C for 20 minutes. Next, a cyclohexane solution containing 13 parts by mass of styrene and a cyclohexane solution containing 64 parts by mass of butadiene (concentration: 40% by mass) were added and polymerized at 80° C. for 70 minutes. Next, a cyclohexane solution containing 11 parts by mass of styrene (concentration: 40% by mass) was added, and polymerization was carried out at 85° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as described above had a styrene content of 36% by mass, a polymer block B1 content of 23% by mass, a vinyl bond amount in polymer block B2 before hydrogenation of 50%, and a weight average molecular weight of 44,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (b-5).

[0124] <Hydrogenated copolymer (b-6)> Batch polymerization was carried out using a tank-type reactor (internal volume: 100 L, charged cyclohexane: 36 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 12 parts by mass of styrene was added. Next, 0.136 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.6 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 65°C for 20 minutes. Next, a cyclohexane solution containing 13 parts by mass of styrene and a cyclohexane solution containing 64 parts by mass of butadiene (concentration: 40% by mass) were added and polymerized at 80° C. for 70 minutes. Next, a cyclohexane solution containing 11 parts by mass of styrene (concentration: 40% by mass) was added, and polymerization was carried out at 85° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 36% by mass, a polymer block B1 content of 23% by mass, a vinyl bond amount in polymer block B2 before hydrogenation of 41%, and a weight average molecular weight of 68,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (b-6).

[0125] <Hydrogenated copolymer (b-7)> Batch polymerization was carried out using a tank-type reactor (internal volume: 100 L, charged cyclohexane: 36 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 12 parts by mass of styrene was added. Next, 0.136 part by mass of n-butyllithium per 100 parts by mass of the total monomers and 2.0 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 65°C for 20 minutes. Next, a cyclohexane solution containing 13 parts by mass of styrene and a cyclohexane solution containing 64 parts by mass of butadiene (concentration: 40% by mass) were added and polymerized at 80° C. for 70 minutes. Next, a cyclohexane solution containing 11 parts by mass of styrene (concentration: 40% by mass) was added, and polymerization was carried out at 85° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as described above had a styrene content of 36% by mass, a polymer block B1 content of 23% by mass, a vinyl bond amount in polymer block B2 before hydrogenation of 77%, and a weight average molecular weight of 68,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (b-7).

[0126] <Hydrogenated copolymer (b-8)> Batch polymerization was carried out using a tank-type reactor (internal volume: 100 L, charged cyclohexane: 36 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 12 parts by mass of styrene was added. Next, 0.136 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.8 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 65°C for 20 minutes. Next, a cyclohexane solution containing 77 parts by mass of butadiene (concentration: 40% by mass) was added, and polymerization was carried out at 80° C. for 70 minutes. Next, a cyclohexane solution containing 11 parts by mass of styrene (concentration: 40% by mass) was added, and polymerization was carried out at 85° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 23% by mass, a polymer block B1 content of 23% by mass, a vinyl bond amount in polymer block B2 before hydrogenation of 51%, and a weight average molecular weight of 68,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (b-8).

[0127] <Hydrogenated copolymer (b-9)> Batch polymerization was carried out using a tank-type reactor (internal volume: 100 L, charged cyclohexane: 36 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 12 parts by mass of styrene was added. Next, 0.136 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.8 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 65°C for 20 minutes. Next, a cyclohexane solution containing 21 parts by mass of styrene and a cyclohexane solution containing 56 parts by mass of butadiene (concentration: 40% by mass) were added and polymerized at 80° C. for 70 minutes. Next, a cyclohexane solution containing 11 parts by mass of styrene (concentration: 40% by mass) was added, and polymerization was carried out at 85° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 44% by mass, a polymer block B1 content of 23% by mass, a vinyl bond amount in polymer block B2 before hydrogenation of 48%, and a weight average molecular weight of 68,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (b-9).

[0128] <Hydrogenated copolymer (b-10)> Batch polymerization was carried out using a tank-type reactor (internal volume: 100 L, charged cyclohexane: 36 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 12 parts by mass of styrene was added. Next, 0.089 part by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.8 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 65°C for 20 minutes. Next, a cyclohexane solution containing 13 parts by mass of styrene and a cyclohexane solution containing 64 parts by mass of butadiene (concentration: 40% by mass) were added and polymerized at 80° C. for 70 minutes. Next, a cyclohexane solution containing 11 parts by mass of styrene (concentration: 40% by mass) was added, and polymerization was carried out at 85° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as described above had a styrene content of 36% by mass, a polymer block B1 content of 23% by mass, a vinyl bond amount in polymer block B2 before hydrogenation of 50%, and a weight average molecular weight of 104,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (b-10).

[0129] <Hydrogenated copolymer (b-11)> Batch polymerization was carried out using a tank-type reactor (internal volume: 100 L, charged cyclohexane: 36 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 12 parts by mass of styrene was added. Next, 0.136 parts by mass of n-butyllithium per 100 parts by mass of the total monomers and 0.45 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 65°C for 20 minutes. Next, a cyclohexane solution containing 13 parts by mass of styrene and a cyclohexane solution containing 64 parts by mass of butadiene (concentration: 40% by mass) were added and polymerized at 80° C. for 70 minutes. Next, a cyclohexane solution containing 11 parts by mass of styrene (concentration: 40% by mass) was added, and polymerization was carried out at 85° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as described above had a styrene content of 36% by mass, a polymer block B1 content of 23% by mass, a vinyl bond amount in polymer block B2 before hydrogenation of 36%, and a weight average molecular weight of 68,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (b-11).

[0130] <Hydrogenated copolymer (b-12)> Batch polymerization was carried out using a tank-type reactor (internal volume: 100 L, charged cyclohexane: 36 L) equipped with a stirrer and a jacket. First, a cyclohexane solution containing 12 parts by mass of styrene was added. Next, 0.136 part by mass of n-butyllithium per 100 parts by mass of the total monomers and 2.3 mol of N,N,N',N'-tetramethylethylenediamine per 1 mol of n-butyllithium were added, and polymerization was carried out at 65°C for 20 minutes. Next, a cyclohexane solution containing 13 parts by mass of styrene and a cyclohexane solution containing 64 parts by mass of butadiene (concentration: 40% by mass) were added and polymerized at 80° C. for 70 minutes. Next, a cyclohexane solution containing 11 parts by mass of styrene (concentration: 40% by mass) was added, and polymerization was carried out at 85° C. for 20 minutes. Thereafter, methanol was added to terminate the polymerization reaction. The copolymer obtained as above had a styrene content of 36% by mass, a polymer block B1 content of 23% by mass, a vinyl bond amount in polymer block B2 before hydrogenation of 83%, and a weight average molecular weight of 68,000. Further, the hydrogenation catalyst prepared as described above was added to the resulting copolymer in an amount of 50 ppm (Ti standard) per 100 parts by mass of the copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80°C. The hydrogenation rate of the resulting hydrogenated copolymer was 98%. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated copolymer to obtain a hydrogenated copolymer (b-12).

[0131] The physical properties of the hydrogenated copolymer (a) are shown in Table 1, the physical properties of the hydrogenated copolymer (b) are shown in Table 2, and the composition and properties of the thermoplastic elastomer composition using the hydrogenated copolymer (X) are shown in the following Tables 3 to 5.

[0132] [Table 1]

[0133] [Table 2]

[0134] [Table 3]

[0135] [Table 4]

[0136] [Table 5]

[0137] From Tables 3 to 5, it is clear that in Examples 1 to 18, there was no score of "1" in terms of wear resistance, processability, and balance of various performances, and thus they were excellent. In Comparative Examples 1 to 12, some of the samples were given a score of "1" in terms of wear resistance, processability, and balance of various performances, and were therefore found to be inferior. [Industrial Applicability]

[0138] The thermoplastic elastomer composition using the hydrogenated copolymer (X) of this embodiment is suitable for various clothing. The present invention has industrial applicability in a wide range of fields, including packaging for various foods, packaging for daily necessities, packaging for industrial materials, lamination for various rubber products, resin products, leather products, etc., industrial products such as elastic tapes and dicing films used in paper diapers, adhesive protective films used to protect building materials and steel plates, base materials for adhesive films, components for drinking water (tubes, hoses, gaskets), sheet products such as trays for fresh meat and fish, fruit and vegetable packs, and frozen food containers, home appliance applications such as televisions, stereos, and vacuum cleaners, materials for automobile interior and exterior parts such as bumper parts, body panels, side seals, and interior (instrument panels, door trims, airbag covers, etc.) skin materials, road paving materials, waterproofing materials, waterproof sheets, civil engineering packing, daily necessities, leisure goods, toys, industrial goods, furniture, writing utensils, stationery such as transparent pockets, holders, and file spines, and medical equipment such as infusion bags and tubes (including catheters).

Claims

1. Hydrogenated polymers containing vinyl aromatic monomer units and conjugated diene monomer units A hydrogenated copolymer (X) containing a copolymer (a) and a hydrogenated copolymer (b), The hydrogenated copolymer (a) contains vinyl aromatic monomer units and conjugated diene monomer units. 、 A polymer block having a vinyl aromatic monomer unit content of 25% by mass or more and less than 80% by mass. has QA2, The amount of vinyl bonds in the polymer block A2 of the hydrogenated copolymer (a) before hydrogenation is 1 mol % or less. at most 40 mol % or less, The weight average molecular weight of the hydrogenated copolymer (a) is 100,000 or more, 70 mol % or more of the total conjugated diene monomer units of the hydrogenated copolymer (a) are hydrogenated. And, The hydrogenated copolymer (b) contains vinyl aromatic monomer units and conjugated diene monomer units. a polymer block having a vinyl aromatic monomer unit content of 1% by mass or more and less than 25% by mass; B2, The amount of vinyl bonds in the polymer block B2 of the hydrogenated copolymer (b) before hydrogenation is 40 mol%. or more and 80 mol % or less, The weight average molecular weight of the hydrogenated copolymer (b) is less than 100,000; The mass ratio of the content of the hydrogenated copolymer (a) to the content of the hydrogenated copolymer (b) ( a) / (b) is 1 / 99 to 99 / 1; Hydrogenated copolymer (X).

2. The hydrogenated copolymer (X) according to claim 1, A thermoplastic resin and / or a rubbery polymer; A thermoplastic elastomer composition comprising:

3. A molded article of the thermoplastic elastomer composition according to claim 2.

Citation Information

Patent Citations

  • Hydrogenated copolymer and its composition

    JP2006117879A

  • Hydrogenated block copolymer composition

    JP2006213853A

  • Hydrogenated block copolymer, hydrogenated block copolymer composition and heat-shrinkable film thereof

    JP2007008984A

  • Rubber composition for tire and pneumatic tire

    JP2013100449A

  • Hydrogenated copolymer, hydrogenated copolymer composition, foamed body, and molded body

    JP2020152779A